Affective responses during 8 weeks of fasted or fed moderate aerobic exercise—a randomized controlled trial - F. Hofstätter; M. Niedermeier; L. K. Rausch; J. S. Lawley; M. Kopp (Cogent Psychology)
Aerobic exercise and time restricted feeding (TRF) are common lifestyle interventions to improve and maintain physical fitness and psychological health. How these interventions interact with each other regarding longer-term psychological effects remains to be investigated. The study aimed to examine how TRF might influence effects of an aerobic exercise intervention on perceived exertion and affective responses. Fifty-two participants were randomized into three groups1) TRF whereby training sessions were performed in the fasted state (FG); 2) TRF whereby training sessions were performed after consuming a standardized carbohydrate-based snack (FFG); 3) one exercise only control group (CG). For 8 weeks participants trained 3x/week for 60 min at a heart rate that corresponded to their individual maximum rate of fat oxidation. Parameters of interest were ratings of perceived exertion (RPE), affective valence (FS) and felt arousal (FAS). Data were collected after 15 and 60 minutes each session. Multi-level modelling was used for data analyses. Thirty-six participants were included in the analyses. Factor time led to significant changes in all parameters (p < .001). Significant group differences were found in RPE (F2,570 = 38.43, p < .001), in FS (F2,563 = 7.47, p < .001) and FAS (F2,563 = 8.08, p < .001). No group × time interactions were found in any parameters. Our data suggest that combining daily TRF and aerobic exercise might lead to higher overall RPE scores for FFG only, higher overall FS scores and lower FAS for both fasting groups when compared to CG.